2016
DOI: 10.1145/2856821
|View full text |Cite
|
Sign up to set email alerts
|

Inner Source Definition, Benefits, and Challenges

Abstract: Inner Source (IS) is the use of open source software development practices and the establishment of an open source-like culture within organizations. The organization may still develop proprietary software but internally opens up its development. A steady stream of scientific literature and practitioner reports indicates the interest in this research area. However, the research area lacks a systematic assessment of known research work: No model exists that defines IS thoroughly. Various case studies provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…19 Organizations do this by introducing new tools to enable "open" practices inside the organization, such as living documents, ordered software repositories, and community development projects. 20 This lets them leverage some of the practical collaborative benefits of open systems without worrying about opening up sensitive internal information or assets to the public. 21 Much research has focused on the impact of Inner Source on software reuse in firms.…”
Section: Why Inner Source?mentioning
confidence: 99%
“…19 Organizations do this by introducing new tools to enable "open" practices inside the organization, such as living documents, ordered software repositories, and community development projects. 20 This lets them leverage some of the practical collaborative benefits of open systems without worrying about opening up sensitive internal information or assets to the public. 21 Much research has focused on the impact of Inner Source on software reuse in firms.…”
Section: Why Inner Source?mentioning
confidence: 99%
“…It would be very interesting to refine the analysis we have done by adding control variables related to different kinds of projects (e.g., small v. large, active v. inactive, mobile apps v. server software v. desktop applications) and development models (e.g., pullrequest based v. direct push, truly distributed v. centralized), to determine whether they contribute differently, and how, to the multiplication of source code artifacts that need tracking. This may lead to insights that would help in addressing provenance tracking at smaller scales that what we have studied here, e.g., in large in-house collaborative development efforts as those being proposed in the context of inner source [11,49].…”
Section: Future Workmentioning
confidence: 99%
“…Noting the success of open source approaches, companies have explored adopting open source software development practices inside their organizations through a set of practices named inner sourcing [5]. Developers working using inner sourcing do not belong to a single project, and anybody in the organization may contribute to all projects in it [25].…”
Section: Related Workmentioning
confidence: 99%
“…For companies building closedsource software with confidential information and intellectual property, inner source offers new techniques and models for encouraging internal collaboration by applying open-source best practices within organizations [12,13]. Studies examining the impact of inner sourcing found potential benefits such as increased development efficiency, higher code quality, and quicker development cycles [5].…”
Section: Related Workmentioning
confidence: 99%